The community structure of forensically important flies and beetles on an altitudinal gradient on Gunung Ulu Kali, Peninsular Malaysia / Thary Bin Gazi - Gazi, Thary (2014)
While present in crime scenes and succession studies, little is known about the ecology and taxonomy of forensically important necrophagus beetles. Natural gradients such as mountains were used to determine how certain groups of animals react to changes in the environment. A survey of forensically important beetles was conducted along an altitudinal gradient on Gunung Ulu Kali using pitfall trapping. The corresponding diversity of blowflies was collected in the same site. Thirty three species of beetles were recorded, with the highest species richness found in the lowland forest at 200m. The beetle and fly communities above 1000m height had less diversity and with different species types than those below that altitude. Four species of Hybosoridae made up most of the collection in lowland forests, few specimens were found in transitional forests. Scarabaeid species could be divided into transitional forest dwellers and lowland forest dwellers. Only one species of Silphidae was collected, however this species displayed a wide altitudinal range. The high coefficient of variation in distribution on a microhabitat spatial scale suggests that aggregation in patches may facilitate species coexistance. The genera Chrysomya, Lucilia and Phumosia made up the majority of flies collected. Chrysomya spp. were mainly lowland and transitional forest species, while Lucilia were found in larger numbers in montane forests. The first of its kind on local species, a taxonomic key for common necrophagus beetle species was constructed based on the specimens collected and from previous forensic succession studies for use by forensic entomologists.